Evaluating Active Labour Market Policies in Türkiye by Regions via Multidimensional Scaling and Clustering Analysis - Özlem Demir; Batuhan Ersöz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Unemployment causes significant problems in society and governments develop different policies to mitigate unemployment. Active labour market policies (ALMP), which are among such policies, constitute crucial instruments for the re-adaptation of the unemployed to the labour markets. However, significant social groups and regional differences occupy an essential role while formulating the programmes. Moreover, economic, cultural, and political factors are also effective in labour force participation rates. Therefore, regarding the participation of social groups such as women, youth, and disabled individuals in employment, ALMP represents a policy instrument that enables a connection between the needs of the labour market and the demands of these groups. The factors affecting the structural characteristics of employment are also applies to regional differences, and many factors ranging from economic development levels of regions to cultural differences have an impact on participation in ALMP programmes. In this study, regional similarities and differences of female, male, and total participation in ALMP programmes in Türkiye according to NUTS-I classification are examined using multidimensional scaling and K-means clustering analysis. Given the importance of the differences between women and men in participation levels in employment, relevant analyses have also been carried out focusing on gender differentiation at the regional level. According to the results of the study, it is observed that Southeast Anatolia (TRC) is significantly separated from other regions in terms of total participation rates. On the other hand, when participation rates are analysed based on unemployment, different regional clusters are encountered and the West Black Sea Region (TR8) is differentiated from other regions. Moreover, different clustering patterns are also observed at the regional scale in the participation of women and men in the programmes.